A Potential Role of Alpha-7 Nicotinic Acetylcholine Receptor in Cardiac Angiogenesis in a Pressure-Overload Rat Model - Min Ni; Zhong-Wei Yang; Dong-Jie Li; Quan Li; Shu-Hui Zhang; Ding-Feng Su; He-Hui Xie; Fu-Ming Shen (Elsevier, 2010)
Abstract.: This work investigated the expression of alpha-7 nicotinic acetylcholine receptor (α7nAChR) in the left ventricle and its putative role in cardiac angiogenesis in a pressure overload rat model induced by abdominal aorta coarctation. Blood pressure and protein levels of α7nAChR were measured at 4, 8, 12, and 16 weeks after surgery. mRNA levels of α7nAChR, cardiac vagus nerve function, cardiac hypertrophy, and microvessel density of the left ventricle were determined at the final 16-week period. The role of α7nAChR in angiogenesis was evaluated. It was found that systolic blood pressure above the coarctation site was greater at 16 weeks after coarctation and expression of α7nAChR was significantly increased at both mRNA and protein levels in the left ventricle compared with the control. Positive staining for receptors was mainly focused around vessels and among the degenerated cardiomyocytes. Cardiac vagus nerve function was significantly attenuated; microvessel density was markedly increased and was associated with cardiac hypertrophy. Activation of α7nAChR induced tube formation of cultured human umbilical vein endothelial cells (HUVECs). We conclude that expression of α7nAChR was increased at 16 weeks after coarctation, and this might be a compensatory response to decreased vagus nerve function and cardiac hypertrophy and may also play a role in cardiac angiogenesis. Keywords:: alpha-7 nicotinic acetylcholine receptor (α7nAChR), cardiac vagus nerve, cardiac hypertrophy, cardiac angiogenesis